DESCRIPTION OF THE NUTRITIONAL STATUS OF STUDENTS IN SD NEGERI 3 PELIATAN, SUBDISTRICT UBUD, GIANYAR - Ayu Indah Hapsari; Putu Yuniadi Antari; Luh Seri Ani (Universitas Udayana, 2013)
Elementary school student are the group of student that potentialy having problem with nutrition due to their eating patern and development status. The cases of malnutrition in Ubud is still highly noted even if Ubud is kown as well-developed subdistrict. The aimed of the study is to descript the nutritional status and other factors related to among the students of SD Negeri 3 Peliatan, Subdistrict Ubud, Gianyar. This study was done on August 19th 2011 until August 20th 2011 and the study design was a cross-sectional. Subjects were the grade 5th and 6th students with a total of 70 student, were chosen by quota sampling technique. Every subject was asked to administer questionnaire, to get the informaton on characteristic, eating pattern and breakfast habit. Antropometric measurements were done to gain the nutritional status of sampel. History of low birth weight was collected from the parents through administering self-administered questionnaires. The data was analysed descriptively. Result showed that subjects tend to have high malnutrition cases, in whom 25.7% were undernutrition and 24.3% were overnutrition 24.3%. Majority of subjects who have good nutritional status were those who admitted to have balanced eating pattern and breakfast habit. In addition, subjects with good nutrition status tended to have good academic scores and those with history of low birth weight seemed to have good and over nutritional status. As the students of SD Negeri 3 Peliatan seemed to have remarkable problem of malnutrition, it is suggested to inform their parents regarding the best eating pattern and to emphasize the importance of berakfast habit to achieve and maintain the good nutritional status for their children.